2012
DOI: 10.1002/jsfa.5797
|View full text |Cite
|
Sign up to set email alerts
|

The probiotic Lactobacillus rhamnosus BFE5264 and Lactobacillus plantarum NR74 promote cholesterol efflux and suppress inflammation in THP‐1 cells

Abstract: Our study shows that Lactobacillus rhamnosus BFE5264 and Lactobacillus plantarum NR74 activated LXR and induced cholesterol efflux by promoting expression of ABCA1 and ABCG1. Both strains also suppressed proinflammatory cytokines including IL-1β and TNF-α. This study could account for the observation that LAB may block foam cell formation by cholesterol efflux and immune modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
16
1
1
Order By: Relevance
“…rhamnosus BFE5264 and L . plantarum NR74 also promote cholesterol efflux and inhibit expression of inflammatory cytokines such as IL-1β and TNF-α, which are increased by LXR activation [ 33 ]. In particular, these two strains activated LXR and induced cholesterol efflux by promoting the expression of ABCA1 and ABCG1.…”
Section: Discussionmentioning
confidence: 99%
“…rhamnosus BFE5264 and L . plantarum NR74 also promote cholesterol efflux and inhibit expression of inflammatory cytokines such as IL-1β and TNF-α, which are increased by LXR activation [ 33 ]. In particular, these two strains activated LXR and induced cholesterol efflux by promoting the expression of ABCA1 and ABCG1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a clinical trial in patients over 65 years old found that the ox-LDL level is inversely proportional to the number of Lactobacilli [ 96 ]. In addition, Yoon et al found that Lactobacillus rhamnosus BFE5264 and Lactobacillus plantarum NR74 may block foam cell formation by cholesterol efflux and immune modulation in THP-1 macrophage cells [ 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strain reduced cholesterol uptake in Caco-2 cells by downregulating the expression of NPC1L1, a critical factor for intestinal cholesterol absorption (3), and increasing cholesterol efflux in CHO-K1 cells by promoting the expression of ATP-binding cassette transporter A1 (ABCA1) and ATP-binding cassette transporter G1 (ABCG1) (4). These genes are the target genes for the cholesterol homeostasis regulators LXRα and LXRβ.…”
Section: Genome Announcementmentioning
confidence: 99%